Potential Acetylcholinesterase, Lipase, α-Glucosidase, and α-Amylase Inhibitory Activity, as well as Antimicrobial Activities, of Essential Oil from Lettuce Leaf Basil (Ocimum basilicum L.) Elicited with Jasmonic Acid - Urszula Złotek; Kamila Rybczyńska-Tkaczyk; Monika Michalak-Majewska; Małgorzata Sikora; Anna Jakubczyk (Applied Sciences, 2020)
The aim of this study was to investigate the influence of the elicitation with jasmonic acid on the biological activities of essential oils (EOs) from lettuce leaf basil (Ocimum basilicum L.). Specifically, 0.01 µM jasmonic acid (JA1), 1 µM jasmonic acid (JA2), and 100 µM jasmonic acid (JA3) were used as elicitors. The results indicated that the elicitation increased the acetylcholinesterase, lipase, and α-amylase inhibitory activity of essential oils. A significant difference in α-glucosidase inhibition was noted only for the JA3 extract (IC50 = 0.81 µL/mL), as this activity was lower than in the control sample without elicitation (IC50 = 0.68 µL/mL). The studied basil EOs exhibited similar activity against Staphylococcus aureus (Gram-positive bacteria) and Escherichia coli (Gram-negative bacteria). Based on the value of the minimum inhibitory concentration (MIC) and the minimum bactericidal concentrations (MBC), the best antimicrobial activity was observed for JA2 and JA3.